Insights into the Urogymnid whiprays (Chondrichthyes: Batoidea) in the Persian Gulf and the Gulf of Oman, with an amendment of their diagnostic characteristics and dispersal range - Golzarianpour, Kiavash; Malek, Masoumeh; Golestaninasab, Mehdi; Sarafrazi, Alimorad; Kochmann, Judith; Klimpel, Sven (Zootaxa, 2020)
Correct identification of elasmobranch species is crucial for taxonomic and parasitological research. Although molecular barcoding may be the fastest choice to determine the identity of a given species, robust and fast species level identification in the field using morphological characters is essential. During this study, 389 specimens representing seven stingray species (Brevitrygon walga, Himantura leoparda, H. uarnak, Maculabatis randalli, M. arabica, M. gerrardi and Pateobatis fai) were examined from the Persian Gulf and the Gulf of Oman. A 1044 bp fragment of the NADH2 gene was generated for 50 specimens with representatives of all species. To verify the initial morphological identification and to compare intra- and interspecific differences a Neighbor-Joining analysis was conducted using uncorrected p-distances, whereas the Bayesian Inference was used to examine the relationships among taxa. Two species (M. arabica and M. gerrardi) are documented from the Persian Gulf for the first time. The molecular results provide the first known evidence of the sympatric distribution of M. randalli and M. arabica in the north and northwestern Indian Ocean. The results of the Bayesian Inference support the recent divergence of both species. Based on morphological comparisons and molecular support we suggest that the descriptions of M. randalli and M. arabica have been carried out on heterogeneous type series which has led to inconsistency between molecular identification and diagnostic morphological characteristics. Detailed morphological examination revealed that there is a relation between the type and number of denticles on the mid-dorsal surface of the disc and the color pattern of the tail. To address this taxonomic conflict all type materials should be re-examined. The Bayesian Inference tree showed that all specimens from the Persian Gulf and the Gulf of Oman morphologically resembling B. walga were found to group well outside those of the Indian species (B. imbricata) with an average p-distance of 0.097. The low nucleotide differences among the urogymnid taxa (P. fai and H. leoparda) from the Persian Gulf and the Gulf of Oman and their conspecific specimens in the Indo-West Pacific region revealed that philopatric behaviors may cause considerable gene flow among populations.